The Identification and Implementation of Key Characteristics of Exemplary Career and Technical Education Programs in Rural Areas - Davis, Kimberly (ProQuest Dissertations & Theses, 2020)
The increased demand for a skilled workforce has placed new challenges on rural school districts. Students are provided the opportunity to obtain the skills required to fill the workforce needs through exemplary career and technical education programs. The purpose of this study was to identify key characteristics of exemplary career and technical education programs in rural areas using the criteria for the Advance CTE Excellence in Action Award as the basis for the study.The descriptive case study design allowed the researcher to provide a rich illustration of exemplary career technical education programs through the eyes of key stakeholders. Data collection from multiple sources included (1) interviews with key stakeholders including career technical directors and career technical program teachers; (2) field observations of students, teachers, and administrators in the identified programs; (3) archival data such as career readiness indicator reports, core indicator reports, and student placement reports from participant career technical education centers in rural Alabama.Findings from this study indicated that six of the eight criteria used for the Advance CTE Excellence in Action Award were directly evident in the data collected through the interviews with career technical directors and teachers. While one of the remaining two criteria was evident in the documents analyzed during the triangulation of data, the other remaining criteria were implied by the structure and progression of the programs.The findings of this study indicate that high-quality career and technical education programs included 1) partnerships with industry, education, and community members, 2) college and career readiness, 3) a real-world environment, 4) specific program characteristics including programs of study that provide a rigorous and relevant curriculum which integrates academic and technical skills creating a clear pathway through secondary education to postsecondary education or the workforce. The findings of this study also included additional elements of exemplary career and technical education. These additional elements were 1) integration of career and technical student organizations, 2) evaluation and 3) specific program characteristics. These additional specific program characteristics included 1) scheduling flexibility, 2) keeping the program facilities and equipment up-to-date, 3) passionate teachers, 4) guidance and relevant professional development for CTE teachers, 5) collaboration across programs, and 6) appropriate student recruitment and placement were all deemed elements of high-quality career and technical education.While the elements identified in exemplary career and technical education were seen across all rural areas, the implementation was often determined by the location. The differences in implementation were most often due to distance from industry and post-secondary institutions, lack of transportation, and funding.